SMAD4 promotes EMT in COPD airway remodeling induced by cigarette smoke through interaction with O-GlcNAc transferase - Ziteng Wang; Yu Ding; Pei Wang; Jinyan Yu; Shulun Huang; Lingjia Yang; Hongjing Gong; Zhen Yu; Rongguo Lu; Tao Bian; Yan Wu (Ecotoxicology and Environmental Safety)
Cigarette smoke (CS) is a prevalent chemical indoor air contaminant known to be the primary cause of EMT during airway remodeling in COPD. While some evidence indicates the involvement of SMAD4 in EMT across certain diseases, its specific role in CS-induced EMT in airway remodeling associated with COPD is not established. In our research, we observed a substantial upregulation in SMAD4 expression, O-GlcNAcylation and EMT in patients with COPD, as well as in vitro and in vivo COPD models induced by CS, than those of the controls. Downregulation of SMAD4 resulted in a reduction in CS-induced EMT in vitro and in vivo. As a post-translational modification of proteins, O-GlcNAcylation is dynamically controlled by the duo of enzymes: O-linked N-acetylglucosamine (O-GlcNAc) transferase (OGT) and O-GlcNAcase (OGA). We further discovered the enhancement of O-GlcNAcylation levels induced by CS was due to an elevated OGT expression, as the expression of OGA remained unchanged. Using an OGT inhibitor (OSMI-1) counteracted the effects of SMAD4 on EMT. Whereas, overexpressing OGT increased SMAD4 expression and promoted EMT. OGT-mediated SMAD4 O-GlcNAcylation shielded SMAD4 from proteasomal degradation by reducing its ubiquitination, thereby aiding in SMAD4 stabilization in response to EMT induced by CS. Overall, this research uncovers a fresh pathway for CS-induced EMT in the airway remodeling of COPD and offers valuable insights.